2010
DOI: 10.1007/s10347-010-0226-0
|View full text |Cite
|
Sign up to set email alerts
|

Cobbles colonization pattern from a tsunami-affected coastal area (SW Thailand, Andaman Sea)

Abstract: We studied the sclerobiont community associated with organogenic and lithic cobbles from soft bottoms in the Khao Lak coastal area (Andaman Sea) that was damaged by the 2004 tsunami. The 15 cobbles examined originate from grab and hand sampling carried out in the years 2006 and 2007 in the depth range of 4.6-15.2 m. A rich endo-and epibenthos was identiWed, mainly consisting of algae, foraminifers, sponges, cnidarians, polychaetes, bryozoans and bivalves. Associations on each examined cobble show similarities … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 28 publications
1
4
0
Order By: Relevance
“…No influence of the 2004 Indian Ocean tsunami has been found within the sediments of seafloor types B and C. This supports the findings of Sanfilippo et al (2010), who reported a minor influence on corals living on cobbles in these areas. These areas seem to be mostly unaffected by the tsunami event.…”
Section: Identification Of Offshore Tsunami Impactsupporting
confidence: 89%
See 2 more Smart Citations
“…No influence of the 2004 Indian Ocean tsunami has been found within the sediments of seafloor types B and C. This supports the findings of Sanfilippo et al (2010), who reported a minor influence on corals living on cobbles in these areas. These areas seem to be mostly unaffected by the tsunami event.…”
Section: Identification Of Offshore Tsunami Impactsupporting
confidence: 89%
“…2). Cobbles from this area, which are covered by colonies of organisms indicating a stable environment, were recently reported by Sanfilippo et al (2010). Additionally, the acoustic base is situated just beneath the surface north and south of Pakarang Cape (Fig.…”
Section: Geological Features Of the Inner Continental Shelfmentioning
confidence: 54%
See 1 more Smart Citation
“…The Bogliasco C is presently growing within the infralittoral Posidonia meadow, with its upper, best-lit side dominated by filamentous and fleshy algae, with subordinate Peyssonneliales and CCA. Bryozoans are also important contributors, especially on sides D and F, together with annelids, confirming their preference for the shadowed and protected substrates (Rosso and Sanfilippo, 2009;Sanfilippo et al, 2011), including the lower surface of calcareous laminar algae.…”
Section: External Componentsmentioning
confidence: 77%
“…In this bed, although most carbonates has been dissolved, a large number of invertebrate specimens have been preserved as molds that exhibit an exceptional degree of preservation, recording a complex community of invertebrates that grew on the inside of the Panopea shells. Nowadays, in soft substrates, scattered small hard-substrate settings, such as large clasts and exoskeletons of marine organisms, may become hot-spots of biodiversity (Kauffman 1978;Kidwell 1986;Sanfilippo et al 2011). These "benthic islands" provide sessile benthic organisms with a relatively stable habitat in an otherwise unstable "ocean" of unconsolidated sediment (Brett 1988;Taylor & Wilson 2003).…”
Section: Introductionmentioning
confidence: 99%